Family counseling: a need for the attention of 8-11 year old children with social disadvantage - Yoelvis Hernández-Ramírez; Eudis Milán-Leyva (Universidad de Guantánamo, 2013)
The diagnosis performed showed inadequacies in the preparation of families to care for children 8-11 years exploiting the potential of recreational sport and physical activities from the community context that allowed the need to plan new ways and forms depending on transform the initial situation. The results obtained in the method of consultation with specialists reflect the feasibility for implementation in social practice and the need and importance of providing better care for these families to enhance educational treat their children with these characteristics.